2016
DOI: 10.1002/malq.201200089
|View full text |Cite
|
Sign up to set email alerts
|

Computable randomness and betting for computable probability spaces

Abstract: Abstract. Unlike Martin-Löf randomness and Schnorr randomness, computable randomness has not been defined, except for a few ad hoc cases, outside of Cantor space. This paper offers such a definition (actually, several equivalent definitions), and further, provides a general method for abstracting "bit-wise" definitions of randomness from Cantor space to arbitrary computable probability spaces. This same method is also applied to give machine characterizations of computable and Schnorr randomness for computable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 112 publications
0
31
0
Order By: Relevance
“…Intuitively, whilst the value of IPI is affected by its previous values, the trend and rate of change are influenced by both physiological and contextual factors, activities, emotions and etc. Martingale Stochastic Process [50] has been used in many applications of randomness such as extraction [51], developing computable randomness [52], algorithmic randomness theory [53] or even stock market analysis [54]. However, it has not been used to extract the randomness from IPI trend.…”
Section: Martingale Randomness Extraction For Ipi (Mre-ipi)mentioning
confidence: 99%
“…Intuitively, whilst the value of IPI is affected by its previous values, the trend and rate of change are influenced by both physiological and contextual factors, activities, emotions and etc. Martingale Stochastic Process [50] has been used in many applications of randomness such as extraction [51], developing computable randomness [52], algorithmic randomness theory [53] or even stock market analysis [54]. However, it has not been used to extract the randomness from IPI trend.…”
Section: Martingale Randomness Extraction For Ipi (Mre-ipi)mentioning
confidence: 99%
“…is finite for all k since M n (ω) is unboundedly large. Then using the definitions of (N n ) and τ k , we have [20]). An a.e.…”
Section: Proofmentioning
confidence: 99%
“…(4) ⇒ (3): Let ω be as in (2) ⇒ (1), except swap the columns and rows. This ω is still Schnorr random since Schnorr randomness is preserved by computable permutations of bits [20]. For ξ ∈ 2 N×N , label the first column as ξ (0) = (ξ 0,0 , ξ 0,1 ξ 0,2 .…”
Section: Doob Schnorr and Computable Randomnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Bienvenu and Porter [4] and independently Rute [30] showed that randomness conservation does not hold for computable randomness [ Bienvenu and Porter asked if no-randomness-from-nothing holds for Schnorr and computable randomness.…”
Section: Introductionmentioning
confidence: 99%